2017
DOI: 10.20959/wjpr20178-9104
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Pelletization Techniques Used in Multiparticulate Drug Delivery System

Abstract: Pharmaceutical research are increasingly focusing on new delivery systems which enhances desired therapeutic objective and therefore minimising side effects. The multiparticulate drug delivery systems are suitable for oral formulation to achieve controlled or delayed release. It has advantages like low dose dumping, flexibility of blending to attain different release pattern and for short gastric residence time. Therefore multiparticulate drug delivery system (MPDDS) provides opportunities in designing control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…31 Melt-granulates enable a slower medication release over longer timespan than standard granulation methods. Drug loading, processability, and overall repeatability may all be improved by combining lipid excipients with various melting points 32 .…”
Section: Melt Granulation/melt Pelletizationmentioning
confidence: 99%
“…31 Melt-granulates enable a slower medication release over longer timespan than standard granulation methods. Drug loading, processability, and overall repeatability may all be improved by combining lipid excipients with various melting points 32 .…”
Section: Melt Granulation/melt Pelletizationmentioning
confidence: 99%
“…Calotropis procera, a member of the Apocynaceae family, is a softly wooded, perennial shrub with few stems, branches, and leaves that are concentrated near the growing tip and have antimicrobial, anthelmintic, antioxidant, antimalarial, nematocidal, anticancer, antiinflammatory properties 43,44 . A study indicated that Calotropis procera leaf powder and amprolium had comparable activity against coccidiosis in chickens 46 .…”
Section: Calotropis Procera (Madar)mentioning
confidence: 99%